2019
DOI: 10.1007/s00221-019-05589-w
|View full text |Cite
|
Sign up to set email alerts
|

Error monitoring and daily life executive functioning

Abstract: Error monitoring during task execution is reflected in post-error slowing (PES), which refers to the tendency to slow down performance after making an error in order to prevent future mistakes. The key question of the present study is whether poor error monitoring (reduced magnitude of PES) has negative consequences for daily life executive function skills, as well as functioning in different life settings such as work, family, social, and academic settings. Eighty-five university students performed a lexical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 81 publications
0
9
0
Order By: Relevance
“…Error‐monitoring, an individual's ability to detect an incorrect response and subsequently adjust to improve future behavior, is an essential skill to achieve successful goal‐directed behavior (Mohamed, Börger, Geuze, & van der Meere, 2019; Rabbitt & Rodgers, 1977). Individual differences in error‐monitoring may be related to personality traits and transdiagnostic psychopathology symptoms, such as worry, negative affect, impulsivity, and conscientiousness (Hill, Samuel, & Foti, 2016; Moser, Moran, & Jendrusina, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Error‐monitoring, an individual's ability to detect an incorrect response and subsequently adjust to improve future behavior, is an essential skill to achieve successful goal‐directed behavior (Mohamed, Börger, Geuze, & van der Meere, 2019; Rabbitt & Rodgers, 1977). Individual differences in error‐monitoring may be related to personality traits and transdiagnostic psychopathology symptoms, such as worry, negative affect, impulsivity, and conscientiousness (Hill, Samuel, & Foti, 2016; Moser, Moran, & Jendrusina, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Notably, the association with everyday functioning was evident when everyday abilities were measured by time to complete an objective, performance-based functional task and by self- and informant-report questionnaires. Prior research with university students has similarly found an association between error monitoring and everyday behaviors including daily planning abilities (Mohamed et al, 2019) and academic achievement (Hirsh & Inzlicht, 2010).…”
Section: Discussionmentioning
confidence: 95%
“…This article is intended solely for the personal use of the individual user and is not to be disseminated broadly. planning abilities (Mohamed et al, 2019) and academic achievement (Hirsh & Inzlicht, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…We analyzed the ERN latency and amplitude for channels Fz, F1, F2, FCz, FC1, and FC2 ( Dan Glauser and Scherer, 2008 ; Cohen, 2011 ; Cavanagh et al, 2012 ; Mohamed et al, 2019 ). The minimum peak in the [0 100] ms interval, where the ERN is reported to be elicited ( Falkenstein et al, 2000 ), was selected.…”
Section: Experimental Methodologymentioning
confidence: 99%
“…Performance monitoring neuronal processes are widely investigated using electroencephalography (EEG) through several event-related potentials (ERPs) – as the error-related negativity (ERN), correct-related negativity (CRN), and error-related positivity (Pe) – and midfrontal theta. Such performance monitoring neuronal markers have been related to behavior adaptation ( Cohen, 2011 ), executive functioning ( Mohamed et al, 2019 ), subjective emotional feeling ( Dan Glauser and Scherer, 2008 ), and attentional control ( Cavanagh et al, 2012 ). Moreover, some of them are believed to be altered in several neuropsychiatric disorders, including depression, schizophrenia, and autism ( Olvet and Hajcak, 2008 ; Bates et al, 2009 ; Santesso et al, 2011 ).…”
Section: Introductionmentioning
confidence: 99%